The World was Going our Way : The KGB and the Battle for the Third World - Andrew, Christopher; Mitrokhin Vasili (New York Basic Books, 2005)
Presents a history of KGB Cold War operations in Asia, Africa, the Middle East, and South America, documenting attempts by the Soviet intelligence service to discredit the United States and foster anti-Americanism in those regions.
Include Map, Illustrations, Notes, Bibliography and Index.
In 1992 the British Secret Intelligence Service exfiltrated from Russia a defector whose presence in the West remained a secret until the publication of The Sword and the Shield in 1999. That man was Vasili Mitrokhin, the KGB's most senior archivist.
Keywords: Soviet Union -- Intelligence service -- Soviet Union. Komitet gosudarstvennoĭ bezopasnosti